Evaluasi Perencanaan Umum Pengadaan Barang/ Jasa Pemerintah pada Universitas Brawijaya - Hidayat, Arif (Jurnal Ilmiah Administrasi Publik, 2019)
The success of the procurement is influenced by the planning of procurement that are well contained in the procurement plan. From the procurement history in Universitas Brawijaya it is known that there is a gap between planning and implementing procurement. This study aims to uncover and evaluate problems related to procurement planning in the University of Brawijaya environment while providing solutions to overcome these problems. Problems were revealed through in-depth interviews with procurement management officials. There are four sources of problems related to the procurement plan. Universitas Brawijaya leaders must give more intense attention to the procurement planning process so that these problems can be reduced